The Effect of Ultrafast Heating on Cold-Rolled Low Carbon Steel: Formation and Decomposition of Austenite - Schulz-Eglin, B; Monsalve-Gonzalez, A; Artigas-Abuin, A; Castro-Cerda, F (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
The effect of heating rate on the formation and decomposition of austenite was investigated on cold-rolled low carbon steel. Experiments were performed at two heating rates, 150 ˚C/s and 1500 ˚C/s, respectively. The microstructures were characterized by means of scanning electron microscopy (SEM) and electron backscattered diffraction (EBSD). Experimental evidence of nucleation of austenite in α/θ, as well as in α/α boundaries is analyzed from the thermodynamic point of view. The increase in the heating rates from 150 ˚C/s to 1500 ˚C/s has an impact on the morphology of austenite in the intercritical range. The effect of heating rate on the austenite formation mechanism is analyzed combining thermodynamic calculations and experimental data. The results provide indirect evidence of a transition in the mechanism of austenite formation, from carbon diffusion control to interface control mode. The resulting microstructure after the application of ultrafast heating rates is complex and consists of a mixture of ferrite with different morphologies, undissolved cementite, martensite, and retained austenite. © 2016 by the authors; licensee MDPI, Basel, Switzerland.